1995
DOI: 10.2172/188537
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of sealing methods and materials used in the salt and potash mining industries

Abstract: Sealing methods and materials currently used in salt and potash industries were surveyed to determine if systems analogous to the shaft seal design proposed for the Waste Isolation Pilot Plant (WIPP) exist. Emphasis was first given to concrete and then expanded to include other materials. Representative case studies could provide useful design, construction, and performance information for development of the WIPP shaft seal system design. This report contains a summary of engineering and construction details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additional analogue observations regarding bulkheads in Canada and other case studies are reported by Eyermann, Van Sambeek, and Hansen (1995). An experience at the Rocanville mine involved drift seal construction of brine-based concrete, analogous to possible panel closure construction for a salt repository room or panel.…”
Section: Full-scale Damage Healing In Saltmentioning
confidence: 92%
“…Additional analogue observations regarding bulkheads in Canada and other case studies are reported by Eyermann, Van Sambeek, and Hansen (1995). An experience at the Rocanville mine involved drift seal construction of brine-based concrete, analogous to possible panel closure construction for a salt repository room or panel.…”
Section: Full-scale Damage Healing In Saltmentioning
confidence: 92%
“…Different studies on the long-term compressive strength of concrete made with seawater discovered that there is almost no difference to that of concrete mixed with freshwater [50][51][52]. Other mixtures of concrete and salt were developed for the protection of radioactive waste in abandoned salt caves [53][54][55][56][57], here salt comprised around 50% of the whole mass [53].…”
Section: Salt Materials In Building Constructionmentioning
confidence: 99%